2014
DOI: 10.1063/1.4886275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the organic halide salt on final perovskite composition for photovoltaic applications

Abstract: The methylammonium lead halide perovskites have shown significant promise as a low-cost, second generation, photovoltaic material. Despite recent advances, however, there are still a number of fundamental aspects of their formation as well as their physical and electronic behavior that are not well understood. In this letter we explore the mechanism by which these materials crystallize by testing the outcome of each of the reagent halide salts. We find that components of both salts, lead halide and methylammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 40 publications
11
74
1
Order By: Relevance
“…MAPbI 3−x Cl x obtained from PbCl 2 :MAI (1:3) and MAPbI 3 from PbI 2 :MAI (1:1) show nearly identical XRD patterns that correspond to a MAPbI 3 phase. This suggests that ion exchange occurs between I and Cl during perovskite film formation [19,177]. This observation is also consistent with previous studies on MASnX 3 perovskite crystals, where it was shown that iodide and chloride elements cannot form a continuous mixed MASnI 3−x Cl x phase as a result of the extremely low solubility of chloride in the MASnI 3 phase [178].…”
Section: Precursor Stoichiometrysupporting
confidence: 90%
“…MAPbI 3−x Cl x obtained from PbCl 2 :MAI (1:3) and MAPbI 3 from PbI 2 :MAI (1:1) show nearly identical XRD patterns that correspond to a MAPbI 3 phase. This suggests that ion exchange occurs between I and Cl during perovskite film formation [19,177]. This observation is also consistent with previous studies on MASnX 3 perovskite crystals, where it was shown that iodide and chloride elements cannot form a continuous mixed MASnI 3−x Cl x phase as a result of the extremely low solubility of chloride in the MASnI 3 phase [178].…”
Section: Precursor Stoichiometrysupporting
confidence: 90%
“…to understand the underlying crystallization process. 14 While a comprehensive understanding of the single step perovskite deposition process already exists, 15 less attention has been given to the more versatile 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 2-step deposition approach. Recently, various alterations to the basic 2-step deposition have been proposed in order to improve photovoltaic performance and reproducibility of devices.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…Several groups studied the role of lead precursors, like PbI 2 , PbCl 2 and PbAc 2 . [19,[27][28][29] www.advancedsciencenews.com presence of chloride, either through methylammonium chloride (MACl) or PbCl 2 , the crystallization kinetics seem to change dramatically. This is further discussed in Section 2.3.…”
Section: One-step (Solvent Engineering)mentioning
confidence: 99%